Iceland Report. Sustainable Governance Indicators 2022 ... - EyÞórsson, Gretar Þór; Gylfason, Thorvaldur; Jahn, Detlef (Bertelsmann Stiftung, 2022)
In the parliamentary election in September 2021, the cabinet coalition of the Left-Green Movement, the Independence Party and the Progressive Party, which has been in office since 2017, won a renewed mandate and remained in office, reshuffling some ministries among the coalition partners. ...